Commonness: beyond the partition paradigm in Palestine-Israel - Guediri, Kaoutar (2019)
This research attempts to examine alternative visions for the Palestine Question. Indeed for decades, the two-state solution based on the principle of partition has been presented as the most realistic and desirable solution to the Palestine Question. However, the reality on the ground has shown that partition is far from being applied and one state had de facto been ruling over the whole country and both populations: the state of Israel. This in turn leads us to question why. As a matter of fact, the partition solution has overlooked the very nature of the Zionist movement which besides being a national movement is also a settler-colonial movement. Thus, the discourse on territorial partition has been accompanied by one on populations’ separation as well as the partition of history and the isolation of the various anti-partition and unitarian visions and propositions that have risen throughout the 20th and the 21st Centuries. The latter became stories as opposed to real(istic) History. The goal of this paper is to address the persistence of anti-partitionist and common perspectives. As a matter of fact, although dispersed in time and space, initiatives and projects advocating one-statist solutions to the Palestine-Israel conflict (one-state, bi-national state, state of all its citizens, secular democratic state, etc…) remind us of the persistence of anti-partitionist perspectives as part of a de-colonisation process. This research is very important because the growing number of initiatives advocating for the end of the two-state solution calls for scrutiny as they, indeed, offer a glimpse of a paradigm (re)shift from partition to anti-partition and commonness. This study focuses on a) assessing the importance of addressing the Palestine Question through the framework of settler colonial studies, b) dressing a historical continuity in anti-partition perspectives, c) analysing anti-partitionism and setting the framework for commonness. In terms of methodology, for this paper, I will be using both empirical and non-empirical research, we may analyse and document experiences of and calls for forms of commonness in the past and present. This research aims at providing tools that could serve the exercise of conceptualisation of reconciliation as well as the imagination of a common future beyond separation and partition, beyond settler-colonialism